YAP and WWTR1: New targets for skin cancer treatment. (28th June 2017) - Andl, Thomas; Zhou, Linli; Yang, Kun; Kadekaro, Ana Luisa; Zhang, Yuhang
Abstract: The core components of the Hippo signaling pathway are a cascade of kinases that govern the phosphorylation of downstream transcriptional co-activators, namely, YES-associated protein (YAP) and WW domain-containing transcription regulator protein 1 (WWTR1, also known as TAZ). The Hippo signaling pathway is considered an important tumor-suppressor pathway, and its dysregulation has been noted in a variety of human cancers, in which YAP/WWTR1 enable cancerous cells to overcome contact inhibition, and to grow and spread uncontrollably. Interestingly, however, recent studies have told a somewhat different but perhaps more intriguing YAP/WWTR1 story, as these studies found that YAP/WWTR1 function as a central hub that integrates signals from multiple upstream signaling pathways, cell–cell interactions and mechanical forces and then bind to and activate different downstream transcriptional factors to direct cell social behavior and cell–cell interactions. In this review, we present the latest findings on the role of YAP/WWTR1 in skin physiology, pathology and tumorigenesis and discuss the statuses of newly developed therapeutic interventions that target YAP/WWTR1 in human cancers, as well as their prospects for use as skin cancer treatments. Highlights: Skin cancer is the most common of all human cancers. YAP and WWTR1 activity are regulated by a complex network of molecules and pathways. YAP1 and WWTR1 contribute to skin cell activity and may play important roles in skin health and skin diseases. The specific oncogenic or tumor suppressor roles of YAP and WWTR1 in skin cancer remain to be further characterized. Targeting YAP/WWTR1 can be achieved at cellular steps that control phosphorylation, translocation, and transcription.